THE SOCIAL MANDATE FOR HIGH SCHOOL - Olga L. Lushnikova (National Research Mordova State University, 2016)
Introduction: the problem of formulation of social mandate at the level of primary education is caused by integration, globalisation processes, and introduction of reforms in education. The contemporary society puts forward new requirements to education system which has to meet demands of various social actors, involved in the educational process. Social mandate is a tool of interaction between society and education by which the diverse consumers of educational services can express their educational needs. A student as the main subject of education takes the special place among the consumers of educational services. Clearly defined social mandates ensures quality of education, therefore this article focuses on the attempt of formulating social mandate for the high school on behalf of a learner. Materials and Methods: a theoretical analysis of pedagogical and sociological literature was made in the process of writing the article. Results: the domestic and international experience in elaboration of the social mandate for the high school was explored and summarised. The main targets of social mandate at the level of basic education was analysed. Discussion and Conclusions: the paper describes the specifics of formulation of the social mandate (specific interests, needs, requirements and requests to high school), that high school should work towards to be able to maintain its competitiveness in the modern market society.